Peramalan curah hujan di Provinsi Aceh menggunakan metode Box-Jenkins - Nurhafifah, Nurhafifah; Patriardian, Ferdy; Hidayati, Alfy; Alzahira, Ratu Rahil; Tasyant, Deva Jhuandra; Anwar, Samsul (Majalah Ilmiah Matematika dan Statistika, 2023)
Floods are one of the natural disasters that frequently occur in Indonesia, including in Aceh Province. Floods primarily occur when rainfall is intense, mainly in the rainy season. Flood disaster management in Aceh Province is still not optimal, so efforts are required to minimize the negative effects of the flood disaster. One of the efforts that can be done is to predict the rainfall that may occur in the future. This study aims to predict rainfall in Aceh Province in 2022 and 2023. The data employed are monthly rainfall data in Aceh Province from 2014 to 2021. The forecasting method employed to predict rainfall is the Autoregressive Moving Average (ARMA) model. Forecasting results using the ARMA (8,6) model show that rainfall in Aceh Province in 2022 and 2023 are predicted to tend to be intense in March, April, May, September, October and November. The Aceh government together with the district/city governments need to prepare anticipatory steps, for example by cleaning water flows like ditches and rivers and socializing about the dangers of flooding and its causes, especially for people living in watersheds. These actions are expected to minimize the potential for flooding in Aceh Province in the future, especially when rainfall is predicted to be intense. Keywords:Aceh Province, box-jenkins, flood, forecasting, rainfallMSC2020:62M10